DESCRIPTION OF THE LEVEL KNOWLEDGE OF PREGNANT WOMEN ABOUT EARLY DETECTION OF DANGER SIGNS OF PREGNANCY IN THE WORK AREA OF TELAGA DEWA HEALTH CENTER BENGKULU CITY - Hilda Septiani; Novianti; Linda Yusanti; Yetti Purnama; Fitri Ramadhaniati (INTERNATIONAL JOURNAL OF MIDWIFERY RESEARCH, 2025)
Backround : Maternal Mortality Rate (MMR) can be defined as the number of maternal deaths in a certain period per 100,000 live births in the same period, which occur in women during pregnancy or within 42 days after the end of pregnancy, regardless of the duration and location of the pregnancy. MMR in Indonesia has experienced a significant decline per 100,000 KH in 2010 to 189 per 100,000 KH in 2020 or a decrease of 45% in the last 10 years. Danger signs of pregnancy are signs that can identify dangers that can occur during pregnancy which if not reported or detected can cause death to the mother. The purpose of this study was to determine the level of knowledge of pregnant women about early detection of danger signs of pregnancy in the work area of the Telaga Dewa Health Center, Bengkulu City. Method : Descriptive research method, namely the researcher describes or provides an overview of the object being studied based on the data obtained. The data source in this study consists of primary data using a questionnaire. The sample in this study a mounted to 110 pregnant women obtained using the Slovin formula with the Quota sampling technique. Result :  The results of the study The description of the level of knowledge of pregnant women in the work area of the Telaga Dewa. Health Center, Bengkulu City showed that the highest level of knowledge was in the good category (70%), sufficient knowledge (23.6%), and insufficient knowledge (6.4%). Conclusion : Based on the results of the study, it was found that pregnant women with good knowledge were 70% and those with insufficient knowledge were 6.4%. It is hoped that this study can help become a reference for further researchers to further examine the level of knowledge of pregnant women about early detection signs of pregnancy dangers in a complex manner